PTEN deficiency mediates a reciprocal response to IGF-1 and mTOR inhibition - Patel, Mukund (Mol Cancer Res, 2014)
Recent evidence implicates the insulin-like growth factor (IGF) pathway in development of Ewing Sarcoma, a highly malignant bone and soft tissue tumor that primarily affects children and young adults. Despite promising results from preclinical studies of therapies that target this pathway, early phase clinical trials have shown that a significant fraction of patients do not benefit, suggesting that cellular factors determine tumor sensitivity. Using FAIRE-seq, a chromosomal deletion of the PTEN locus in a Ewing sarcoma cell line was identified. In primary tumors PTEN deficiency was observed in a large subset of cases, although not mediated by large chromosomal deletions. PTEN loss resulted in hyper-activation of the AKT signaling pathway. PTEN rescue led to decreased proliferation, inhibition of colony formation, and increased apoptosis. Strikingly, PTEN loss decreased sensitivity to IGF-1R inhibitors but increased responsiveness to temsirolimus, a potent mTOR inhibitor, as marked by induction of autophagy. These results suggest that PTEN is lost in a significant fraction of primary tumors and this deficiency may have therapeutic consequences by concurrently attenuating responsiveness to IGF-1R inhibition while increasing activity of mTOR inhibitors. The identification of PTEN status in the tumors of patients with recurrent disease could help guide the selection of therapies.